2021
DOI: 10.18176/jiaci.0596
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis After Cutaneous Application of Argan Oil

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the case of our observation, the specific IgE assay was not performed due to lack of resources. The oral provocation test remains a reference examination to authenticate an allergy to Argan oil; it consists in ingesting the food with increasing quantities up to the dose usually consumed; it is done in a hospital under rigorous supervision [12]. The provocation test carried out in our child concluded that he was allergic to Argan oil.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the case of our observation, the specific IgE assay was not performed due to lack of resources. The oral provocation test remains a reference examination to authenticate an allergy to Argan oil; it consists in ingesting the food with increasing quantities up to the dose usually consumed; it is done in a hospital under rigorous supervision [12]. The provocation test carried out in our child concluded that he was allergic to Argan oil.…”
Section: Discussionmentioning
confidence: 91%
“…Cases of rhinitis, conjunctivitis related to the smell of Argan oil, and cases of epigastralgia and hypersalivation upon ingestion of Argan oil [8]. It should be mentioned that two cases of acute hypersensitivity pneumonitis have been reported in cosmetic workers exposed to Argan powders [9]. The allergen identified in Argan oil allergy is an 11S globulin protein of 10KDA, which crosses with peanut, sesame and hazelnut allergens [10].…”
Section: Discussionmentioning
confidence: 99%